2018
DOI: 10.1103/physrevb.97.195438
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-induced superconductivity in a topological insulator coupled to ferromagnetic and antiferromagnetic insulators

Abstract: We study the effective interactions between Dirac fermions on the surface of a three-dimensional topological insulator due to the proximity coupling to the magnetic fluctuations in a ferromagnetic or antiferromagnetic insulator. Our results show that the magnetic fluctuations can mediate attractive interactions between Dirac fermions of both Amperean and BCS type. In the ferromagnetic case, we find pairing between fermions with parallel momenta, so-called Amperean pairing, whenever the effective Lagrangian for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…We write ψ σ ≡ ψ σ (τ, r i ) and ψ σ ≡ ψ σ (τ , r j ), and the same convention for a, b, and J A, B (r i ). Let us first consider a general type of interface, and use H int in (8). The interface structure is then encoded in the spatial dependencies of J A, B (r i ).…”
Section: A One Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…We write ψ σ ≡ ψ σ (τ, r i ) and ψ σ ≡ ψ σ (τ , r j ), and the same convention for a, b, and J A, B (r i ). Let us first consider a general type of interface, and use H int in (8). The interface structure is then encoded in the spatial dependencies of J A, B (r i ).…”
Section: A One Interfacementioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].Research interest in antiferromagnetic materials is surging [11,12]. This enthusiasm is due to the promising properties of antiferromagnets such as high resonance frequencies in the THz regime and a vanishing net magnetic moment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent related study, the cases of a TI coupled to a FMI and a TI coupled to an antiferromagnetic insulator (AFMI) were considered in Ref. [14]. Possible attractive interactions for both Amperean and BCStype pairing were found.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, magnons in the magnet can mediate electron-electron attraction in the conducting layer. The resulting magnon-mediated superconductivity has been investigated theoretically in normal metals [19,20] as well as topological insulators [21,22], and experimentally [23]. Magnon-mediated indirect exciton condensation has also been predicted recently [24].…”
mentioning
confidence: 99%